filter structure

JP2026166579APending Publication Date: 2026-10-14NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059590
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166579000001_ABST
    Figure 2026166579000001_ABST
Patent Text Reader

Abstract

To provide a filter structure with improved shape retention. [Solution] The filter structure 100 of the present invention includes a filter 10 having a filter substrate 11 and a plurality of ventilation paths 15, and a cured product 20 of a curable composition that covers at least a part of the surface of the filter 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a filter structure.

Background Art

[0002] In recent years, carbon capture and storage (CCS) and carbon capture and utilization (CCU) have been studied to reduce the amount of carbon dioxide in the atmosphere. In CCS and CCU, carbon dioxide may be recovered by separating carbon dioxide from the atmosphere.

[0003] As a method for separating acidic gases such as carbon dioxide, a technology for directly separating and recovering carbon dioxide contained in the atmosphere, exhaust gas, or the like (DAC: Direct Air Capture) has attracted attention. For example, Patent Document 1 describes a method for separating gaseous carbon dioxide from a gas mixture containing gaseous carbon dioxide and a gas different from carbon dioxide by adsorption / desorption using an adsorbent. In Patent Document 1, desorption of gaseous carbon dioxide is performed by heating an adsorption structure having an adsorbent that has adsorbed gaseous carbon dioxide to a temperature in the range of 80°C to 130°C and bringing it into contact with water vapor.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] As described in Patent Document 1, in DAC, the adsorbent is exposed to a high-temperature and high-humidity environment. The conventional technology has room for improvement from the viewpoint of shape retention in such a harsh environment.

[0006] The present invention aims to provide a filter structure with improved shape retention. [Means for solving the problem]

[0007] The present invention A filter having a filter substrate and multiple ventilation paths, A cured product of a curable composition that covers at least a portion of the surface of the filter, A filter structure is provided that includes [this]. [Effects of the Invention]

[0008] According to the present invention, a filter structure with improved shape retention can be provided. [Brief explanation of the drawing]

[0009] [Figure 1] This is a perspective view showing an example of the filter structure of the present invention. [Figure 2] This is a cross-sectional view of the filter structure shown in Figure 1. [Figure 3] This is a schematic cross-sectional view showing a modified example 1 of the filter in the filter structure. [Figure 4] This is a schematic cross-sectional view showing a modified example 2 of the filter in the filter structure. [Figure 5] This is a schematic cross-sectional view showing a modified example 3 of the filter in the filter structure. [Modes for carrying out the invention]

[0010] A filter structure according to a first aspect of the present invention is A filter having a filter substrate and multiple ventilation paths, A cured product of a curable composition that covers at least a portion of the surface of the filter, Includes.

[0011] In the second aspect of the present invention, for example, in the filter structure according to the first aspect, the filter is in contact with the cured product.

[0012] In the third aspect of the present invention, for example, in the filter structure according to the first or second aspect, the curable composition contains a curable resin.

[0013] In the fourth aspect of the present invention, for example, in the filter structure according to any one of the first to third aspects, the filter is a honeycomb structure.

[0014] In the fifth aspect of the present invention, for example, in the filter structure according to any one of the first to fourth aspects, the filter has a structure in which a plurality of sheet-shaped filter base materials are laminated.

[0015] In the sixth aspect of the present invention, for example, in the filter structure according to the fifth aspect, the filter base material has a flat plate shape or a corrugated shape.

[0016] In the seventh aspect of the present invention, for example, in the filter structure according to any one of the first to sixth aspects, the filter base material contains a polymer having an amino group.

[0017] In the eighth aspect of the present invention, for example, in the filter structure according to the seventh aspect, the polymer has a structural unit derived from an epoxy compound and a structural unit derived from an amine compound.

[0018] In the ninth aspect of the present invention, for example, in the filter structure according to the seventh or eighth aspect, the filter base material has a three-dimensional network skeleton composed of the polymer.

[0019] In the tenth aspect of the present invention, for example, in the filter structure according to any one of the first to ninth aspects, the filter base material is an acidic gas adsorbent.

[0020] The details of the present invention will be described below, but the following description is not intended to limit the present invention to any particular embodiment.

[0021] <Filter structure> Figure 1 is a schematic perspective view showing an example of a filter structure. The filter structure 100 shown in Figure 1 includes a filter 10 and a cured product 20 of a curable composition that covers at least a portion of the surface of the filter 10. The filter 10 comprises a filter substrate 11 (hereinafter simply referred to as "substrate 11") and has a plurality of ventilation paths 15.

[0022] The filter 10 is typically a honeycomb structure in which multiple ventilation paths 15 extend in the same direction. In Figure 1, the ventilation paths 15 penetrate the filter 10 and open to a pair of opposing main surfaces of the filter 10. In the filter structure 100, the entire surface of the filter 10 excluding the main surfaces (hereinafter referred to as "side surfaces") is covered with a cured material 20. Thus, the cured material 20 is positioned on the surface of the filter 10 in a location where the ventilation paths 15 are not blocked and the filter can function, for example, on a surface parallel to the direction in which the ventilation paths 15 extend.

[0023] It is preferable that the filter 10 and the cured material 20 are in contact. At least a portion of the cured material 20 may be impregnated from the surface (side) to the interior of the filter 10.

[0024] Because the cured material 20 covers the surface of the filter 10, deformation of the filter 10 is suppressed. Therefore, the shape retention of the filter structure 100 is improved.

[0025] The base material 11 is typically an acidic gas adsorbent. Therefore, the filter structure 100 according to the embodiment of the present invention can adsorb acidic gases. Conventional acidic gas adsorption structures (filters) have the problem that when adsorbing / desorbing acidic gases, the acidic gas adsorbent (base material) is exposed to harsh environments of high temperature and high humidity, causing swelling and / or deformation, which leads to the collapse of the structure's shape. The filter structure 100 according to the embodiment of the present invention has improved shape retention.

[0026] [Cured product] The cured product 20 is a cured product of a curable composition. The curable composition contains a curable material (curable material). The curable material may be an organic material or an inorganic material. Examples of curable materials include curable resins and gypsum, and are preferably curable resins. Examples of curable resins include photocurable resins, thermosetting resins and watercurable resins, and are preferably photocurable (ultraviolet curable). Examples of these resins include vinyl ester resins, epoxy resins, silicone resins, urethane resins, phenolic resins, polyester resins, melamine resins and urea resins, preferably vinyl ester resins, epoxy resins, silicone resins, phenolic resins and melamine resins, and more preferably vinyl ester resins, epoxy resins and phenolic resins.

[0027] The curable composition may contain other materials in addition to the curable material. Such materials may be, for example, fillers. The fillers are preferably glass fibers. The curable composition may also contain fiber-reinforced plastic (FRP) as the curable material.

[0028] The cured product 20 is, for example, obtained by placing a sheet-like curable composition on the surface of the filter 10 and curing it, preferably by wrapping the sheet-like curable composition around the side of the filter 10 and curing it. The sheet-like curable composition may be a resin sheet made of the above-mentioned materials, or a sheet made of a curable material, or a curable material and a filler and a support that supports them. Examples of the support include stretched resin sheets and fiber sheets. Another preferred example of the cured product 20 is obtained by coating the surface of the filter 10 with the curable composition and curing it, or by coating the surface of the filter 10 with the curable composition and then wrapping a support around it and curing it.

[0029] As described above, the cured material 20 is preferably a sheet-like member that covers the surface of the filter 10.

[0030] The mass ratio of the cured product 20 in the filter structure 100 is preferably 5% to 95%, more preferably 20% to 70%, and even more preferably 30% to 60%.

[0031] The tensile modulus (Young's modulus) of the cured product 20 is, for example, 1 MPa to 500 GPa, preferably 0.1 GPa to 500 GPa, more preferably 0.5 GPa to 500 GPa, even more preferably 1 GPa to 500 GPa, and particularly preferably 2 GPa to 500 GPa. A cured product 20 that satisfies the above numerical range has sufficient rigidity against the stress caused by the swelling and / or deformation of the filter substrate 11. Therefore, the above configuration can further improve shape retention. In the case where the cured product 20 is obtained by coating the surface of the filter 10 with a curable composition as described above and then wrapping a support around it and curing it, it is desirable that the composite of the cured composition and the support (cured product 20) satisfies the above numerical range.

[0032] The thickness of the cured material 20 covering the surface of the filter 10 is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more. The upper limit of the thickness of the cured material 20 is, for example, 10 mm, preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less.

[0033] The filter structure 100 of this embodiment can be manufactured using a conventional filter (typically an acidic gas adsorbent and an adsorption structure equipped therewith). That is, it can be manufactured by coating the sides of a conventional adsorption structure with the cured material 20, thereby improving shape retention without reducing the adsorption performance of the conventional filter. Furthermore, according to the present invention, by providing the cured material 20, the shape retention of the filter structure 100 can be improved regardless of the shape and dimensions of the filter 10.

[0034] The following provides a more detailed explanation of filter 10.

[0035] [Filter] As described above, the filter 10 comprises a base material 11 and a ventilation path 15. The filter 10 is an acidic gas adsorption structure comprising a base material 11 which is typically an acidic gas adsorbent. The ventilation path 15 functions as a path through which the raw material gas containing the acidic gas passes when the base material 11 adsorbs the acidic gas. In the filter 10, it is preferable that the base material 11 is arranged such that the ventilation path 15 extends in the direction of flow of the raw material gas. It is preferable that the filter 10 is a honeycomb structure having a plurality of ventilation paths 15 extending in the same direction. In this specification, "honeycomb structure" means a structure having a cross-section that tiled a plane with a certain shape such as a polygon, not limited to a regular hexagon. The ventilation path 15 penetrates the filter 10, and a plurality of ventilation paths 15 are arranged parallel to each other. The shape of the cross-section perpendicular to the direction in which the ventilation path 15 extends is not particularly limited.

[0036] Figure 2 is a cross-sectional view of the filter structure 100. Figure 2 shows a cross-section perpendicular to the direction in which the ventilation path 15 of the filter structure 100 extends. The filter 10 in the filter structure 100 shown in Figure 2 is a honeycomb structure.

[0037] The base material 11 preferably has the shape of a sheet.

[0038] In Figure 2, the filter 10 has a structure in which multiple sheet-like substrates 11 are laminated. The filter 10 may include, for example, an adsorption unit U in which a corrugated (wave-shaped) substrate 11A and a flat substrate 11B are laminated. In the substrate 11A, multiple peaks 12 and multiple valleys 13 may be arranged alternately. In this case, a ventilation path 15 is formed between the peaks 12 or valleys 13 of the substrate 11A and the substrate 11B. Thus, the ventilation path 15 may be surrounded by the substrates 11A and 11B. The ventilation path 15 extends along a direction perpendicular to the lamination direction of the substrates 11. In the filter 10 shown in Figure 2, the shape of the cross section perpendicular to the direction in which the ventilation path 15 extends is defined by the peaks 12 or valleys 13 of the substrate 11A and the substrate 11B.

[0039] The thickness of the sheet-like substrate 11 is, for example, 2000 μm or less, and may be 1500 μm or less, 1000 μm or less, 800 μm or less, 500 μm or less, 500 μm or less, and even 250 μm or less. The lower limit of the thickness of the substrate 11 is, for example, 10 μm or more, and may be 50 μm or more, and even 80 μm or more.

[0040] The filter 10 preferably has a structure in which a plurality of sheet-like substrates 11 are laminated together with an adhesive. For example, the filter 10 may be constructed in which substrates 11A and 11B are bonded to each other with an adhesive and laminated alternately.

[0041] Any adhesive can be used. Conventional adsorption structures (filters) have the problem that exposure to harsh environments of high temperature and high humidity causes the adsorbent material (substrate) to swell and / or deform, and a force acts outward on the structure, causing the adhesive bond to easily peel off, thereby causing the structure to lose its shape. In the filter structure 100 according to the embodiment of the present invention, deformation of the filter 10 is suppressed by the cured product 20, making the adhesive bond less likely to peel off and improving shape retention.

[0042] In the filter structure 100, it is preferable that the cured material 20 covers at least the surface parallel to the direction in which the ventilation path 15 extends, and that this surface is parallel to the lamination direction of the base material 11. With this configuration, the cured material 20 can effectively suppress peeling of the adhesive surface and suppress deformation of the filter 10. It is more preferable that the cured material 20 covers the entire surface parallel to the direction in which the ventilation path 15 extends, that is, the entire side surface of the filter 10 (the surface in which the ventilation path 15 is not blocked).

[0043] In this embodiment, the base material 11 preferably contains a polymer P having an amino group.

[0044] The substrate 11 may have a porous structure. For example, the substrate 11 may be a porous body containing polymer P. Preferably, the porous body has a three-dimensional network skeleton containing polymer P. The three-dimensional network skeleton may further contain other components besides polymer P. As an example, in the porous body, the three-dimensional network skeleton extends continuously. Preferably, the pores contained in the porous body are continuous pores formed in a three-dimensional manner. The porous body may have independent pores, or it may have through pores penetrating the porous body. The pores contained in the porous body (more specifically, pores derived from the three-dimensional network skeleton) are of an observable size when observed, for example, using a scanning electron microscope (SEM) at a magnification of 5000x. The average pore diameter of these pores is preferably 0.1 μm or more and 5 μm or less, and more preferably 3 μm or less. In some cases, the substrate 11 may be a non-porous body in which no pores can be observed when observed using an SEM at a magnification of 5000x.

[0045] The substrate 11 may contain polymer P as its main component, or may consist substantially of polymer P alone. In this specification, “main component” means the component that is present in the most abundant amount by weight in the substrate 11 (typically a porous body having a three-dimensional network structure).

[0046] The base material 11 may contain other components in addition to polymer P. Examples of other components include a carrier for supporting polymer P, a reaction accelerator, a plasticizer, a pigment, a dye, an antioxidant, a conductive material, an antistatic agent, an ultraviolet absorber, a flame retardant, and an antioxidant. Reaction accelerators are used, for example, when synthesizing polymer P. Examples of reaction accelerators include tertiary amines such as triethylamine and tributylamine; and imidazoles such as 2-phenol-4-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenol-4,5-dihydroxyimidazole. These reaction accelerators can accelerate the reaction for synthesizing polymer P (reactant P1, described later). Examples of carriers include fibers and fiber structures containing fibers. Examples of fibers include glass fibers; natural fibers such as wood pulp, cotton, and hemp (e.g., Manila hemp); and chemical fibers (synthetic fibers) such as polyester fibers, rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, and polyurethane fibers. Examples of fiber structures include woven fabrics, nonwoven fabrics, and paper. A specific example of a fiber structure is glass paper.

[0047] The polymer P content in the substrate 11 is, for example, 5 wt% or more, and may be 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, or even 35 wt% or more. The higher the polymer P content, the greater the tendency for the amount of acidic gas adsorbed by the substrate 11 to be. The upper limit of the polymer P content is, for example, 80 wt% or less, and may be 60 wt% or less.

[0048] The polymer P content can be measured, for example, by the following method. First, the substrate 11 is placed in a simultaneous thermal analysis DSC / TGA instrument. At this time, the temperature is set to 30°C. Next, using this instrument, the temperature is raised from 30°C to 100°C at a heating rate of 10°C / min under a nitrogen atmosphere and held at that temperature for 40 minutes (Operation 1). According to Operation 1, water contained in the substrate 11 can be removed. Next, the temperature is raised from 100°C to 800°C at a heating rate of 10°C / min and held at that temperature for 5 minutes (Operation 2). According to Operation 2, polymer P can be removed from the substrate 11. The ratio (100 × (W1-W2) / W1) of the difference between the weight W1(g) of the substrate 11 immediately after Operation 1 and the weight W2(g) of the substrate 11 immediately after Operation 2 can be considered as the polymer P content in the substrate 11.

[0049] (Polymer P) Polymer P has an amino group. Preferably, polymer P has a constituent unit U1 derived from an epoxy compound and a constituent unit U2 derived from an amine compound. Polymer P includes, for example, a reactant P1 from a group of compounds including an amine monomer and an epoxy monomer. Reactant P1 may be a polymer of the epoxy compound and the amine compound, or it may be a crosslinked product in which the amine compound is crosslinked by the epoxy compound.

[0050] Examples of amine monomers include ethylamine, ethylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, iminobispropylamine, bis(hexamethylene)triamine, 1,3,6-trisaminomethylhexane, tris(2-aminoethyl)amine, N,N'-bis(3-aminopropyl)ethylenediamine, polymethylenediamine, trimethylhexamethylenediamine, poly Examples include aliphatic amines such as ether diamines; alicyclic amines such as isophorone diamine, menthane diamine, piperazine, N-aminoethylpiperazine, 3,9-bis(3-aminopropyl)2,4,8,10-tetraoxaspiro(5,5)undecane adduct, bis(4-amino-3-methylcyclohexyl)methane, bis(4-aminocyclohexyl)methane, and modified versions thereof; aliphatic polyamines such as polyethyleneimines and polyalkylene polyamines; (meth)acrylic polymers having amino groups such as aminoethylated acrylic polymers; and aliphatic polyamidoamines formed by the reaction of polyamines with dimer acids. Amine monomers can be used alone or in combination of two or more.

[0051] Examples of epoxy monomers include monofunctional epoxy compounds such as n-butyl glycidyl ether, higher alcohol glycidyl ether, allyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, cresyl glycidyl ether, p-sec-butylphenyl glycidyl ether, and t-butylphenyl glycidyl ether; diepoxyalkanes such as 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, and 1,9-decadiene diepoxide; and (poly)ethylene glycol diglycidyl ether. Examples include polyfunctional epoxy compounds having an ether group, such as ether, (poly)propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane polyglycidyl ether, and sorbitol polyglycidyl ether; and polyfunctional epoxy compounds having an amino group, such as N,N,N',N'-tetraglycidylmetoxylendiamine and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane.

[0052] The epoxy monomer may, in some cases, be an aromatic epoxy resin, a non-aromatic epoxy resin, etc. Examples of aromatic epoxy resins include polyphenyl-based epoxy resins, epoxy resins containing fluorene rings, epoxy resins containing triglycidyl isocyanurate, and epoxy resins containing heteroaromatic rings (e.g., triazine rings). Examples of polyphenyl-based epoxy resins include bisphenol A type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, stilbene type epoxy resins, biphenyl type epoxy resins, bisphenol A novolac type epoxy resins, cresol novolac type epoxy resins, diaminodiphenylmethane type epoxy resins, and tetrakis(hydroxyphenyl)ethane-based epoxy resins. Examples of non-aromatic epoxy resins include aliphatic glycidyl ether type epoxy resins, aliphatic glycidyl ester type epoxy resins, alicyclic glycidyl ether type epoxy resins, alicyclic glycidylamine type epoxy resins, and alicyclic glycidyl ester type epoxy resins.

[0053] Epoxy monomers can be used individually or in combination of two or more. When using monofunctional epoxy compounds, it is preferable to use them in combination with other epoxy monomers containing two or more epoxy groups. Monofunctional epoxy compounds can also be used as reactive diluents to adjust the viscosity of the monomer group used to form the reactant.

[0054] The content of constituent unit U1 in polymer P, particularly reactant P1, is, for example, 20 wt% to 70 wt%. The content of constituent unit U2 in polymer P, particularly reactant P1, is, for example, 30 wt% or more, preferably 50 wt% or more. The upper limit of the content of constituent unit U2 is not particularly limited, but is, for example, 80 wt%.

[0055] The glass transition temperature Tg of polymer P is not particularly limited, and is, for example, 40°C or lower, preferably 30°C or lower, more preferably 20°C or lower, even more preferably 15°C or lower, and may be 10°C or lower, 5°C or lower, or 0°C or lower. When the glass transition temperature Tg of polymer P is this low, the rate of adsorption of acidic gases in the substrate 11 tends to be high. The lower limit of the glass transition temperature Tg of polymer P is, for example, -100°C, preferably -50°C, and more preferably -10°C, from the viewpoint of ensuring sufficient adsorption of acidic gases in the substrate 11 and heat resistance. In this specification, the glass transition temperature Tg is the intermediate glass transition temperature (T) determined in accordance with the provisions of JIS K7121:1987. mg This means that polymer P is a solid. Polymer P is typically a thermosetting resin. Polymer P is solid at, for example, 25°C, preferably in the range of 25°C to 80°C.

[0056] The weight-average molecular weight of polymer P is not particularly limited, but is, for example, 500 or more, preferably 1000 or more, more preferably 100000 or more, and even more preferably 100000 or more. The upper limit of the weight-average molecular weight of polymer P is, for example, 10000000 or less.

[0057] [Uses of filter structures] The filter structure 100 according to an embodiment of the present invention is typically an acid gas adsorption structure capable of adsorbing acidic gases. Examples of acidic gases include carbon dioxide, hydrogen sulfide, carbonyl sulfide, sulfur oxides (SOx), hydrogen cyanide, nitrogen oxides (NOx), and preferably carbon dioxide.

[0058] The filter structure 100 can be used, for example, by the following method. First, a mixed gas containing an acidic gas is brought into contact with the filter structure 100 and passed through the ventilation path 15 in the filter 10. This causes the substrate 11 to adsorb the acidic gas contained in the mixed gas. The operation of bringing the mixed gas into contact with the acidic gas adsorbent is carried out, for example, until the adsorption of the acidic gas by the substrate 11 reaches equilibrium. The mixed gas contains, for example, other gases besides the acidic gas. Other gases include, for example, nonpolar gases such as hydrogen and nitrogen, and inert gases such as helium, with nitrogen being preferred. The mixed gas is typically the atmosphere. The mixed gas may also be an off-gas from a chemical plant or a thermal power plant.

[0059] The temperature of the mixed gas is, for example, room temperature (23°C). The concentration of the acidic gas in the mixed gas is not particularly limited, but at standard conditions (0°C, 101kPa), it is, for example, 0.01 vol% (100 vol ppm) or more, preferably 0.04 vol% (400 vol ppm) or more, and may be 1.0 vol% or more. The upper limit of the concentration of carbon dioxide in the mixed gas is not particularly limited, but at standard conditions, it is, for example, 10 vol%. The pressure of the mixed gas is typically equal to the atmospheric pressure in the environment in which the acidic gas adsorbent is used. However, the mixed gas brought into contact with the acidic gas adsorbent may be pressurized.

[0060] Next, the substrate 11 that has adsorbed the acidic gas is subjected to a regeneration process. The regeneration process can be carried out, for example, by heating the filter structure 100. The heating temperature is, for example, 50 to 80°C. The filter structure 100 may be heated under a reduced pressure atmosphere or a vacuum atmosphere. By heating the filter structure 100, the acidic gas is desorbed from the substrate 11. At this time, the filter structure 100 may be brought into contact with water vapor to further desorb the acidic gas. As a result, the substrate 11 is regenerated and the filter structure 100 can be used repeatedly. The acidic gas, especially carbon dioxide, desorbed from the substrate 11 can be used as a raw material for chemical synthesis or as dry ice.

[0061] As described above, in the adsorption / desorption operation of acidic gases, the filter structure 100 is exposed to harsh environments of high temperature and high humidity. The filter structure 100 according to the embodiment of the present invention has improved shape retention in such harsh environments by comprising a cured product 20. As a result, the shape of the ventilation path 15 is maintained, and efficient passage of the mixed gas through the ventilation path 15 and adsorption of acidic gases can be maintained. Therefore, the filter structure 100 according to the embodiment of the present invention can improve adsorption efficiency.

[0062] [Method for manufacturing a filter structure] The filter structure 100 of this embodiment can be manufactured by placing a curable composition on the surface (side surface) of the filter 10 and curing the curable composition to form a cured product 20 on the side surface.

[0063] For example, a sheet-like curable composition may be wrapped around the side of the filter 10 and cured to form a cured material 20 over the entire side surface. Alternatively, the curable composition may be applied to the surface of the filter 10 and the coating film may be cured. In this case, a sheet-like cured material 20 covering the side surface of the filter 10 may be formed by wrapping a support over the applied curable composition and then curing it. When a curable composition is applied to the surface of the filter 10 to form a coating film and then cured to form a cured material 20, the curable composition may impregnate the filter 10 from the surface into the interior. Therefore, in such a case, at least a portion of the cured material 20 may be impregnated into the filter 10 in the filter structure 100.

[0064] An example of a method for manufacturing the substrate 11 and the filter 10 when the substrate 11 constituting the filter 10 is an acidic gas adsorbent having a porous structure is described below.

[0065] First, the above group of compounds, including amine compounds and epoxy compounds, is mixed with a pologen to prepare a mixture. The pologen is a solvent that can dissolve monomers and prepolymers contained in the group of compounds, and furthermore, can induce reaction-induced phase separation after the group of compounds has reacted. Specific examples of pologens include cellosolves such as methyl cellosolve and ethyl cellosolve, esters such as ethylene glycol monomethyl ether acetate and propylene glycol monomethyl ether acetate, glycols such as polyethylene glycol, polypropylene glycol and polyoxyalkylene glycol, and ethers such as polyoxyethylene monomethyl ether and polyoxyethylene dimethyl ether. Specific examples of polyoxyalkylene glycols include poly(1,2-butanediol)-6 propylene glycol and polyoxypropylene diglyceryl ether. The pologen may also be a polar solvent such as ethyl acetate, N,N-dimethylformamide (DMF), acetonitrile, ethanol, isopropanol, a nonpolar solvent such as toluene, or a mixture thereof. Pologens can be used alone or in combination of two or more types.

[0066] Other components besides the compound group may be added to the mixture. Examples of other components include the reaction accelerators mentioned above.

[0067] Next, the compounds are reacted in a mixed solution. For example, the compounds are reacted by applying or impregnating a sheet-like carrier with the mixed solution and then performing a heat treatment. This yields a sheet-like cured material containing polymer P and pologen. In this cured material, a co-continuous structure is formed by the phase separation of polymer P and pologen.

[0068] Next, the pologen is extracted and removed from the cured body. This allows us to obtain a sheet-like acidic gas adsorbent (substrate 11) containing a porous polymer P and a support. The pologen can be extracted, for example, by immersing the cured body in a solvent. Suitable solvents include water, aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, aliphatic alcohol solvents, ester solvents, ether solvents, and halogen-containing organic solvents. Examples of aliphatic hydrocarbon solvents include n-hexane, cyclohexane, methylcyclohexane, n-heptane, n-octane, isooctane, petroleum ether, and benzine. Examples of aromatic hydrocarbon solvents include toluene, xylene, mesitylene, and benzene. Examples of aliphatic alcohol solvents include methanol, ethanol, isopropanol, butanol, cyclohexanol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and diethylene glycol. Examples of ester solvents include ethyl acetate. Examples of ether solvents include diethyl ether, diisopropyl ether, dibutyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, dioxane, and anisole. Examples of halogen-containing organic solvents include dichloromethane, chloroform, carbon tetrachloride, dichloroethane, and chlorobenzene. These solvents can be used individually or in combination of two or more.

[0069] The obtained sheet-like substrate 11 is formed into a corrugated shape, and adhesive is applied to the vertices of the corrugations. By bonding this to a flat sheet-like substrate 11, a corrugated sheet, which is an adsorption unit U, can be produced by laminating the corrugated substrate 11 and the flat substrate 11. Adhesive is applied again to the vertices of the corrugated sheet, and the flat surfaces of the corrugated sheets are overlapped and laminated. By laminating the corrugated sheets until the desired size is reached, a filter 10, which is a honeycomb structure having multiple ventilation paths 15, can be obtained. The corrugated sheets may be cut to the desired size before lamination, or they may be cut into the desired shape while the filter 10 is still laminated.

[0070] The filter 10 in the filter structure 100 is not limited to the example shown in Figure 2. Modifications of the filter 10 will be described below with reference to Figures 3 to 5. These modifications are variations of the honeycomb structure.

[0071] Figure 3 is a schematic cross-sectional view showing modification 1 of the filter 10 in the filter structure 100. The filter 10A shown in Figure 3 is a honeycomb structure having a triangular lattice cross-section formed by tiling triangles in a plane. A ventilation path 15 is formed inside each triangular lattice. In Figure 3, for example, the raw material gas is supplied from the front to the back of the paper. The filter 10A can be manufactured, for example, by combining a flat base material 11B and a sheet-like base material 11C that has been folded into an accordion shape.

[0072] Figure 4 is a schematic cross-sectional view showing a modified example 2 of the filter 10 in the filter structure 100. The filter 10B shown in Figure 4 is a honeycomb structure having a square grid cross-section formed by filling a plane with squares. A ventilation path 15 is formed inside each square grid. In Figure 4, for example, the raw material gas is supplied from the front to the back of the paper. The filter 10B can be manufactured, for example, by stretching a sheet-like substrate 11 that is laminated in multiple layers via appropriately placed adhesives.

[0073] Figure 5 is a schematic cross-sectional view showing a third modified example of the filter 10 in the filter structure 100. The filter 10C shown in Figure 5 is a honeycomb structure having a hexagonal grid cross-section formed by filling a plane with hexagons. A ventilation path 15 is formed inside each hexagonal grid. In Figure 5, for example, the raw material gas is supplied from the front to the back of the paper. The filter 10C can be manufactured, for example, by stretching a sheet-like substrate 11 that is laminated in multiple layers via appropriately placed adhesives.

[0074] The filter structure 100 and filter 10 described above are block-shaped, but the present invention is not limited thereto. In this specification, "block shape" means rectangular parallelepiped shape and cubic shape, and includes those in which the shape defined by the outer edge is rectangular parallelepiped shape and cubic shape. For example, the filter structure of the present invention may have a cylindrical shape. Such a filter may have a shape in which the adsorption unit U, which is made of a base material 11, is wrapped around a central tube. In this case, the multiple peaks and multiple valleys are arranged alternately in the circumferential direction of the filter structure, and the ventilation path penetrates the filter in the direction in which the central tube extends. The side circumference of the cylindrical filter is covered with a cured product of a curable composition.

[0075] Furthermore, the filter 10 does not have to be formed from a sheet-like substrate 11. For example, the filter 10 may be formed by perforating a block made of an amine compound. For example, the filter 10 may be a honeycomb structure made of a porous material such as zeolite. A liquid amine compound may be supported on the honeycomb structure. Alternatively, the filter 10 may be an aggregate of bead-shaped adsorbents. That is, the filter structure 100 may be a structure in which at least a part of the surface of the filter 10, which is a honeycomb structure or aggregate as described above, is covered with a cured product 20.

[0076] The descriptions of each embodiment and each modification described above are interchangeable, insofar as they do not conflict with technical standards. Furthermore, each embodiment and each modification may be combined with each other, insofar as they do not conflict with technical standards. [Examples]

[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto.

[0078] [Example 1] (Preparation of acid gas adsorbent sheets) First, 5.22 g of poly(1,2-butanediol)-6 propylene glycol (NOF Co., Ltd., Uniol® PB-500) and 5.22 g of polyoxypropylene diglyceryl ether (NOF Co., Ltd., Unilube® DGP-700) were added to a 50 mL Labolan screw-cap vial (AS ONE Corporation). 2.55 g of ethylene glycol diglycidyl ether (Nagase ChemteX Corporation, EX-810) and 3.83 g of pentaerythritol tetraglycidyl ether (Showa Denko Corporation, Showfree® PETG) were dissolved in the resulting mixture to prepare a mixture of epoxy monomer and pologen.

[0079] Next, a mixture of epoxy monomer, amine monomer, and pologen was prepared by adding 6.57 g of triethylenetetramine (manufactured by Tosoh Corporation) to this mixture. In this mixture, the ratio (E / A) of the equivalent amount of epoxy groups (E) in the epoxy monomer to the equivalent amount of active hydrogen (A) of the primary amino group in the amine monomer was 0.4.

[0080] Next, a tabletop shaker (Angel Vibrator Digital 60Hz) was set to intensity 5 and the mixture was shaken for 2 minutes. Then, using an applicator with a gap of 500 μm, the mixture was coated onto 250 μm thick glass paper (PHN-50GC, manufactured by Oji F-Tex Co., Ltd.). At this time, the mixture soaked into the glass paper. The mixture was cured by leaving the glass paper soaked in the mixture in a 120°C dryer for 30 minutes. This yielded a sheet-like cured body containing polymer P having amino groups and glass paper as a support. This cured body was immersed in ethyl acetate at 60°C for 30 minutes, and this process was repeated twice with a change of solution. This removed the pologen from the cured body and formed a porous sheet. Next, by drying in a 60°C dryer for 30 minutes, an acidic gas adsorbent sheet (thickness: 0.25 mm), which is a porous sheet containing glass paper as a support, was obtained. The acidic gas adsorbent sheet had a three-dimensional network structure composed of polymer P.

[0081] (Fabrication of honeycomb structures) Next, using the obtained acid gas adsorbent sheet as a base material, a honeycomb structure as shown in Figure 2 was fabricated by the following method. First, one acid gas adsorbent sheet was formed into a corrugated shape using a heated roll. The corrugation pitch P was 3.0 mm and the peak height h was 2.0 mm. Vinyl acetate emulsion adhesive was applied to the vertices of the corrugations and bonded to another flat acid gas adsorbent sheet to obtain a corrugated sheet base material. This corrugated sheet base material was cut to a sheet length of 40 mm and a sheet width of 50 mm. Vinyl acetate emulsion adhesive was applied to the vertices of the corrugations of the cut sheet base materials, and the flat surfaces of the sheet base materials were overlapped to laminate and bond them together, obtaining a laminate with a length of 40 mm, a width of 50 mm, and a height of 50 mm. In this way, a filter, which is a corrugated honeycomb structure in which multiple ventilation paths extend in the same direction and penetrate through, was obtained. The mass of the filter was 18 g.

[0082] (Creation of filter structure) A 1mm thick UV-curing FRP sheet (ES-300L, manufactured by Sanko Techno Co., Ltd.), cut to a width of 50mm, was wrapped around the entire side of the obtained filter (the side parallel to the direction in which the ventilation path extends). The filter was then left outdoors for 2 hours to cure the FRP sheet with ultraviolet rays from sunlight. The same process was repeated to wrap the sheet a total of two times. In this way, a filter structure of Example 1 was obtained in which the entire side circumference of the filter was covered with cured material. The mass of the filter structure of Example 1 was 35g, and the mass ratio of cured material (cured FRP sheet) in the filter structure was 48%.

[0083] (Measurement of the tensile modulus of the hardened material) The tensile modulus of the cured material in the filter structure of Example 1 was measured as follows. The cured material was cut into a 1 cm × 5 cm test piece. The thickness of the test piece was 2 mm. A tensile test was performed on the test piece using an Autograph precision universal testing machine (Shimadzu Corporation, AGX-V) under the following conditions, and the tensile modulus was found to be 1.9 GPa. (conditions) Temperature: 23℃ Tensile direction: Longitudinal direction of the test specimen Initial chuck distance: 20mm Tensile speed: 20 mm / min

[0084] [Example 2] (Preparation of acid gas adsorbent sheets) An acidic gas adsorbent sheet was prepared in the same manner as in Example 1.

[0085] (Fabrication of honeycomb structures) A filter with a corrugated honeycomb structure was fabricated in the same manner as in Example 1.

[0086] (Creation of filter structure) A silicone self-fusing tape (MonotaRO, 55307623, tensile modulus of elasticity (catalog value) 1.6 MPa) measuring 25 mm in width, 0.3 mm in thickness, and 65 cm in length was evenly wrapped around the entire side surface of the obtained filter (the surface parallel to the direction in which the air passage extends) so that the entire side surface was covered. In this way, a filter structure of Example 2 was obtained in which the entire side circumference of the filter was covered with cured material. The mass of the filter structure of Example 2 was 24 g, and the mass ratio of the cured material (silicone self-fusing tape) in the obtained structure was 25%.

[0087] [Comparative Example 1] (Preparation of acid gas adsorbent sheets) An acidic gas adsorbent sheet was prepared in the same manner as in Example 1.

[0088] (Fabrication of honeycomb structures) A corrugated honeycomb structure filter was fabricated in the same manner as in Example 1. The resulting filter was used as the filter structure for Comparative Example 1. In other words, Comparative Example 1 did not involve coating the filter with a cured material.

[0089] <Rating> The filter structures of the examples and comparative examples were subjected to a highly accelerated life test (HAST) by being left to stand for 48 hours in an environment of 105°C and 100% RH.

[0090] After the test, the shape changes of the filter structure and the presence or absence of corrosion were observed, and the filter structure was evaluated using the following indicators. The evaluation results are shown in Table 1. (shape retention) ○: There was almost no change in shape before and after the test. △: Although there were some minor changes in the external shape, no deterioration of the filter due to sheet peeling was observed. ×: The sheet peeled off and the filter fell apart. (corrosion) ○: No corrosion was observed. ×: Corrosion was observed. (comprehensive evaluation) ◎: Both shape change and appearance received a ○ rating. ○: One of the shape change or appearance is rated ○, the other is rated △. △: Both shape change and appearance receive a △ rating. ×: At least one of the shape change or appearance received an × rating.

[0091] [Table 1]

[0092] The filter structures of Examples 1 and 2 exhibited superior shape retention compared to Comparative Example 1. The filter structure of Example 1 exhibited even greater shape retention than that of Example 2. This is presumed to be due to the superior rigidity (elastic modulus) of the cured material covering the sides of the filter.

[0093] The filter structure of this embodiment can improve shape retention without degrading performance. [Industrial applicability]

[0094] The filter structure of this embodiment is suitable for recovering acidic gases, particularly carbon dioxide. [Explanation of Symbols]

[0095] 100 filter structures 10 filters 11 Filter substrate 12 Yamabe 13 Tanibe 15. Ventilation paths 20 Cured product

Claims

1. A filter having a filter substrate and multiple ventilation paths, A cured product of a curable composition that covers at least a portion of the surface of the filter, A filter structure that includes this.

2. The filter structure according to claim 1, wherein the filter and the cured product are in contact.

3. The filter structure according to claim 1, wherein the curable composition comprises a curable resin.

4. The filter structure according to claim 1, wherein the filter is a honeycomb structure.

5. The filter structure according to claim 1, wherein the filter has a structure in which a plurality of sheet-like filter substrates are laminated.

6. The filter structure according to claim 5, wherein the filter substrate is flat or corrugated.

7. The filter structure according to claim 1, wherein the filter substrate comprises a polymer having an amino group.

8. The filter structure according to claim 7, wherein the polymer has structural units derived from an epoxy compound and structural units derived from an amine compound.

9. The filter structure according to claim 7, wherein the filter substrate has a three-dimensional mesh-like skeleton composed of the polymer.

10. The filter structure according to claim 1, wherein the filter substrate is an acidic gas adsorbent.

Citation Information

Patent Citations

  • Steam-Assisted Vacuum Desorption Process for Carbon Dioxide Recovery

    JP2017528318A